Relationships BetweenKnowledge, Attitude, Perceived Self-Efficacy and Capabilities for Basic Life Support among Cardiovascular Disease Caregivers - อินทร์แก้ว ทยุตา; เภารอด ภาวินี; ชัยรัตน์ ดุลย์โสภา (Journal of The Royal Thai Army Nurses, 2019)
This descriptive correlation research aimed to examine the relationships between knowledge, attitude, perceived self-efficacy, and capabilities for basic life support among cardiovascular disease caregivers. A total of 110 cardiovascular disease caregiversat out-patient cardiovascular department were selected using stratified sampling. Data were collected using a questionnaire including the basic life supportknowledge, the attitude towards basic life support, the perceived self-efficacy, and the capabilities to basic life support among cardiovascular disease caregivers. Spearman correlation coefficient was used to analyze the data. The results showed thatthe basic life support knowledge was significantly positively correlated with the attitude towards basic life support, the perceived self-efficacy, and the capabilities to basic life support. In addition, the attitude towards basic life support and the perceived self-efficacy were significantly positively associated with the capabilities to basic life support among cardiovascular disease caregivers. The findings indicated that nurses should provide information and promote positive attitude and self-efficacy towards basic life support among cardiovascular disease caregivers in order to be able to save the life of patients with cardiac arrest in time.